Are you adopting artificial intelligence products? Social-demographic factors to explain customer acceptance - Mariano Méndez Suárez; Abel Monfort; José-Luis Hervás-Oliver (European Research on Management and Business Economics (ERMBE), 2023)
Are consumers accepting AI-based products? What are the socio-demographics influencing the adoption of these products? This study tests the potential users' social-demographic characteristics that influence the relationship between innovation and AI-based products. The latter are robots (e.g. chatbots) and AI (e.g. recommendation systems, amongst others). A mixed methods approach is adopted using both qualitative and quantitative analysis with non-metrical multidimensional scaling (NMDS) to map opinions about digitally-intensive products, such as robots and AI, and the attitude towards innovation. The research uses data on the general population from the Spanish innovation barometer survey (N = 3,005). Findings show that individuals who have a negative attitude towards innovation have a negative opinion about robots and AI. As regards social-demographic dimensions, age and economic conditions moderate this effect, causing a more positive opinion towards digitally-intensive products amongst young people and individuals with a higher socio-economic level. These effects are increased by the moderating role of sex.
Keywords: M21; O21; O31; O33; 650; Robots acceptance; AI-based products; Artificial intelligence; Digitally-Intensive products